Stock Identification Sardinella Lemuru, Bleeker 1853 In Madura Strait, Bali Strait, and Southern-East Java Water - Setyohadi, Daduk; Iranawati, Feni; Hikmah, Syarifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
Balinese Sardinella (Sardinella lemuru) is the main commodity in Indonesia. Despite, more research show that lemuru got the overfishing condition. In East Java region, likely Bali Strait, Southern-East Java water, and Madura Strait are the region which the most production of lemuru catch. So it needs identification stock of Sardinella lemuru on the third fisheries management east java sub-region, as it to be used as a reference to managing the sustainability of the catch sardinella lemuru for the future. Research carried out in January to May 2016 with the methods is the sample of random sampling on three different locations water representing Madura Strait, Bali Strait, and southern-East Java water. The each sample implemented were in four times during a period of months old different. Every the sample researchers get as 50-200 tail. Sardinella lemuru in accordance with the season fish. The sample which has been obtained taken to the laboratory of Marine Science University of Brawijaya to data take. The analysis used in this research was Truss morphometric and Factor analysis of the condition allometric. Based on the results of the analysis in the Madura Strait, Bali Strait, and Southern-East Java water are having a distinction of morphometric character amount 44 % with the character being very affected is PAL_FL, DFB_HL , PVL_FL, UPCL_FL, OD_HL, and PPL_FL. Around 64 % of the whole morphometric character that is 14 characters. Next, if it is seen from Allometric condition in the third these waters having b value different from each aquatic and after B-test that lemuru in the three the waters might otherwise dissimilar stock so management of Sardinella lemuru in the three waters should have been undertaken in separated.